(untitled) (Kronika Bydgoska, 2013)
Activation of a stretch of the Eastern Railway was a breakthrough event for the development of Solec Kujawski. This started the supply of hundreds of thousands of railway sleepers to Solec Kujawski, which - after washing - were sent by railway. In 1873, reloading of railway sleepers gathered momentum and the Eastern Railway Management in Bydgoszcz constructed a railway siding leading to the Vistula River. Industrialist Ruttgers from Dresden established in Solec Kujawski a plant for preservation and treatment of sleepers with tar and tar oil with the use of vacuum-pressure method. At the beginning of World War One, the plant’s productivity varied within 40,000 m3. Railway sleepers were almost 2/3 of the production, and traction poles - 1/3. In the years 1920-1939, the plant belonged to the Polish-German joint stock company: Preserving Plant - Management in Solec Kujawski, and then Preserving Plant Solec Kujawski. In the 1930’s, the plant experienced serious problems connected with an economic crisis. During World War Two and the Nazi occupation, the plant employed forced labourers. After 1945, the plant was nationalised and taken over by the State Railways District Management in Gdańsk as the Polish State Railways Timber Materials Preserving Plant in Solec Kujawski48. The plant preserved timber mainly for the Polish State Railways, and poles for the purpose of electrification of the country.